Significance and Approach of Hydrotropic agent for the estimation of Tolperisone and Diclofenac in the combined solid dosage form By Chemometric method - Deokate, Shivarti V.; Rajgauri S. Shelke,; Snehal S. Maskar,; Gurappa K. Dyade,; Nilesh Jadhav, (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: The aim of the present research was to select common solvent for the solublisation of both drugs. Hydrotopes are surface active, highly water soluble organic salt, which imparts solubility to insoluble or sparingly soluble organic compounds in water, which is when present at moderate to higher concentration.Chemo metric assisted absorption spectrophotometric analytical methodswere developed by using hydrotropes for the estimation of Tolperisone (TPS) and Diclofenac (DFC) from their combined formulation. Materials and Method: Simultaneous equation, Q-absorbance method method were selected from the nature of spectra, solvent 4% urea was utilized. For simultaneous equation method 261 nm and 277 nm was the wavelength for absorbance measurement of TPS and DFC respectively and for Q method wavelength 241 and 261 as λ1 and λ2 respectively was selected. Effect of input variables on spectrum characteristics were studied for selection of critical parameters and developed method was validated as per ICH Q 2 R1 regulatory guidelines. Linearity of the drugs was ascertained over the conc range 1-20 mcg/ml (microgram/ml) for TPS and 1-48 mcg/ml for DFC. Results and Discussion: The percentage purity of assay was found 102.03% for TPS and 97.65% for DFC; and the accuracy study data were varied from 0.1123 to 0.1581for TPS and 0.0554 to 0.1409 for DFC. Precision study was shown acceptable data as SD data varied from 1.108 to 2.6721 for TPS and from 0.8119 to 3.4549 for DFC. Conclusion: Hydrotropic solvents improved solubility of poorly water soluble drug diclofenac. The developed method is rigid, robust and efficient for the estimation of TPS and DFC from the combined formulation.